2020
DOI: 10.7150/jca.41193
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic values of m6A RNA methylation regulators in differentiated Thyroid Carcinoma

Abstract: N6-methyladenosine (m6A) is the most prevalent modification of RNA in mammals. m6A RNA methylation levels are dynamically regulated by m6A RNA methylation regulators. While increasing evidence has suggested that m6A RNA methylation is vital in the initiation and progression of human carcinoma, little is known about the expression and effect of m6A RNA methylation regulators in differentiated thyroid carcinoma (DTC). Herein, we demonstrate that most of the thirteen main m6A RNA methylation regulators are differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…As shown in Figure 1, except the m6A-binding protein, YTHDF2, all other 13 m6A-associated factors were differentially expressed in thyroid cancer tissues ( p < 0.01). This result is consistent with previous research (Xu et al, 2020). Among these 13 m6A-associated factors, the expression levels of binding proteins, HNRNPC and methyltransferase METTL5, in thyroid cancer tissues were higher than those in adjacent nontumor tissues.…”
Section: Expression Of M6a-associated Factors In Thyroid Cancersupporting
confidence: 93%
“…As shown in Figure 1, except the m6A-binding protein, YTHDF2, all other 13 m6A-associated factors were differentially expressed in thyroid cancer tissues ( p < 0.01). This result is consistent with previous research (Xu et al, 2020). Among these 13 m6A-associated factors, the expression levels of binding proteins, HNRNPC and methyltransferase METTL5, in thyroid cancer tissues were higher than those in adjacent nontumor tissues.…”
Section: Expression Of M6a-associated Factors In Thyroid Cancersupporting
confidence: 93%
“…Using similar pipeline, many studies have revealed the diagnostic and prognostic roles of m 6 A or other methylation (e.g., m 1 A) regulators in specific cancer including but not limited to hepatocellular carcinoma [162] , [163] , uveal melanoma [164] , prostate cancer [165] , gynecological cancers [166] , esophageal cancer [167] , thyroid carcinoma [168] and renal carcinoma [169] . Moreover, Meng et al have built the m 6 A-related mRNA signature to predict the prognosis of pancreatic cancer patients [170] and predicted that PAH, ZPLD1, PPFIA3, and TNNT1 genes exhibited an independent prognostic value using correlation and survival analysis.…”
Section: Diagnosis and Prognosis Analysismentioning
confidence: 99%
“…They established different immune-related signatures to predict the prognosis of patients with TC. The remaining thyroid prediction models mainly focused on the study of characteristic gene sets are mainly m6A-related signature 80 , 81 and autophagy-related signature. 82 These results indicate that the characteristic signature not only has a good prediction effect on the prognosis of thyroid cancer patients but is more conducive to the comprehensive interpretation of the occurrence and development of TC and provides a theoretical basis for the use of drugs that act on this characteristic.…”
Section: Discussionmentioning
confidence: 99%